The impact of economic growth on child labour in developing countries - Abdullahi, Idris Isyaku; Mohd Noor, Zaleha (International Institute for Science, Technology & Education, 2015)
Child labouring in developing countries constitutes an alarming proportion of the entire workforce and international organizations and NGOs have suggested ways to curb this problem. This study empirically investigates the relationship between child labour and economic growth in a cross-section of (67) countries over time. A dynamic system GMM approach was adopted and the growth child labour Kuznet curve as presented by Kambhampati &Rajan, (2005) was established. The results shows that economic growth initially increase child labour but as growth is sustained over time, child labour tend to decline in developing countries. This findings suggest serious commitment by governments of the developing countries to promote long term growth in order to curtail the menace of child labour.